THE EXISTENCE OF BATAK ULOS IN THE AREA OF HEGEMONY - Nainggolan, Mangido (E-Journal of Cultural Studies; Volume 13, Number 2, May 2020DO - 10.24843/cs.2020.v13.i02.p01, 2020)
Adat or custom is made by humans for the sake of human interest, it is hoped that the stability and order of the community are maintained through the customs that are imposed on these community groups. Culture will continue to move along with the movement of global economic activity, it also influences the development of every existing culture. The Toba Batak culture is also inseparable from these clashes. The label as an idol worshiper is synonymous with the Toba Batak culture. There are many issues and views that explain why this happened, including the result of local religious practices practiced by the Toba Batak community today such as the Ulus ritual labeled by Charismatic Christian Missionaries as Atheist teachings. According to them, Ulos must be destroyed because it is considered a magic object in which magical powers are attached and “save” the power of evil spirits. The hegemony of modernization and globalization, reinforced by the influence of religion, has made Ulos an object that has high values ??of civilization, starting to erode, especially in terms of the nature and meaning of it. In this regard, the aim of this paper is to explain the existence of Ulos in relation to the hegemony of modernity and the pressure of Charismatic Christian missionaries on the indigenous Batak culture. The data analysis and approach method used in this study is qualitative with the perspective of cultural studies. The results showed that the shift in meaning was getting out of control because the perpetrators were the Batak people themselves who had been exposed to a new ideology that was centered on spiritual issues. The reason that seems so biblical is used as a tool to legalize the extermination in the form of burning Ulos against his followers because Ulos is labeled loaded with demonic powers. The process of eliminating the meaning of the ancestral heritage becomes faster because the adat institutions no longer have the legal power to oppose the hegemony and dominance that continues.  Key words: Ulos Batak, hegemony, charismatic Christianity